Kuonan hallinta yhdistelmäpuhalluskonvertterissa - Koski, Saara; Alamäki, Pekka; Härkki, Jouko (Report / University of Oulu, Department of Process Engineering, ISSN 0783-7747, 1995)
Abstract: The control of slag in the combined blowing converter.